Expert consensus on nutrition and lower-carbohydrate diets: An evidence- and equity-based approach to dietary guidance - Volek, Jeff S.; Yancy, William S.; Gower, Barbara A.; Phinney, Stephen D.; Slavin, Joanne; Koutnik, Andrew P.; Hurn, Michelle; Spinner, Jovonni; Cucuzzella, Mark; Hecht, Frederick M. (Frontiers in Nutrition, 2024)
There is a substantial body of clinical evidence supporting the beneficial effects of lower-carbohydrate dietary patterns on multiple established risk factors associated with insulin resistance and cardiovascular diseases in adult populations. Nutrition and health researchers, clinical practitioners, and stakeholders gathered for, “The Scientific Forum on Nutrition, Wellness, and Lower-Carbohydrate Diets: An Evidence- and Equity-Based Approach to Dietary Guidance” to discuss the evidence base around lower-carbohydrate diets, health outcomes, and dietary guidance. Consensus statements were agreed upon to identify current areas of scientific agreement and spotlight gaps in research, education, and practice to help define and prioritize future pathways. Given the evidence base and considering that most American adults are living with at least one nutrition-related chronic disease, there was consensus that including a lower-carbohydrate dietary pattern as one part of the Dietary Guidelines for Americans could help promote health equity among the general population.